2021
DOI: 10.1007/s10389-021-01604-z
|View full text |Cite
|
Sign up to set email alerts
|

In the digital age: a systematic literature review of the e-health literacy and influencing factors among Chinese older adults

Abstract: Aim This study aimed to explore the current status of e-health literacy among Chinese older adults, and to summarize and analyze the related influencing factors. Subject and methods Following the PRISMA Checklist, we searched MEDLINE, CINAHL Complete (EBSCO), PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, WanFang Data, and China Science and Technology Journal Database to identify the relevant literature published between January 2000 and December 2020. The Mixed Methods Assessment T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 35 publications
4
53
0
Order By: Relevance
“…While there has been a noticeable increase in the number of publications regarding digitalisation, and the health literacy of elderly people in recent years (Shi et al, 2021;Watkins and Xie, 2014). However, there is a lack of studies that holistically examine and synthesise the relationships between health literacy, intervention programmes, use of digital health services, and health decision-making in the context of elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been a noticeable increase in the number of publications regarding digitalisation, and the health literacy of elderly people in recent years (Shi et al, 2021;Watkins and Xie, 2014). However, there is a lack of studies that holistically examine and synthesise the relationships between health literacy, intervention programmes, use of digital health services, and health decision-making in the context of elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that multiple factors affected the eHealth literacy. Shi Y et al [36] divided the in uencing factors into individual-level factors (age, gender, education, economy, frequency of Internet use and trust in online health resources), interpersonal-level factors (marital status, family caregivers and the experience of studying looking for health information) and social/community level factors (language and cultural barriers) based on socio-ecological model with the systematic review methods. Levin-Zamir et al [37] indicated that eHealth literacy was affected by the complexity of the network system.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholder research has suggested that health care providers have recognized that adopting, expanding, and sustaining technology-enabled health care models has generally benefitted patients, clinicians, and health services. These models require robust clinical trials and health service evaluations [26][27][28].…”
Section: The Elements Of Digital Transformation On Public Servicesmentioning
confidence: 99%